Integrasi literasi digital pada desain didaktis: Analisis prospektif pembelajaran aljabar - Fuadiah, Nyiayu Fahriza; Septiati, Ety; Marhamah, Marhamah (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2022)
This study aimed to formulate the Hypothetical Learning Trajectory (HLT) as part of the Didactical Design Research at the prospective analysis stage in the VIII class of Algebra learning, namely the Two-variable Linear Equation System (TVLES). HLT is based on a study of learning obstacles which includes aspects of repersonalization of material content, potential use of digital media in learning, curriculum analysis, and didactic aspects and is adapted to the needs of students and the development of digital literacy. This study involved 47 students of class VIII, 21 students of class IX, 3 mathematics teachers, and 5 model students. Based on a prospective analysis, the HLT on aspects of the TVLES concept is formulated as follows: 1) Considering the concept of “The Meaning of the Equal Sign” through an open context (realtime thinking literacy), recognize variables as unknown values and varying quantities; 2) Completing an open sentence using trial and error through the context of scales (photo visual literacy); 3) revealing the relationship between symbolic representations and straight-line graphs; the meaning of the point of intersection, using algebraic concepts in completing TVLES (branching literacy); 4) create a mathematical model of a problem related to TVLES (information literacy), and; 5) solving various problems related to TVLES through a logical algorithm. This HLT was expected to be developed into a didactic design which will later be implemented in learning.